2019
DOI: 10.1016/j.ijwd.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of interest among dermatology textbook authors

Abstract: BackgroundConflict of interest as it relates to medical education is a burgeoning topic of concern. Dermatology textbooks are an influential resource for dermatologists. This study evaluates industry payments to authors of major dermatology textbooks.ObjectiveThe primary objective of this study is to evaluate whether authors of dermatology textbooks had appreciable conflicts of interest in the form of payments from industry.MethodsThis is a retrospective study in which the authors and editors of eight commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…A further 88.8% (414/466) of physicians in this study received payments from industry. This was higher than the percentage reported for dermatology textbook authors [ 6 ] (54.0%) and the 73.3% and 86% reported in the studies by Feng et al [ 4 ] and Checketts et al [ 23 ], respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…A further 88.8% (414/466) of physicians in this study received payments from industry. This was higher than the percentage reported for dermatology textbook authors [ 6 ] (54.0%) and the 73.3% and 86% reported in the studies by Feng et al [ 4 ] and Checketts et al [ 23 ], respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…In contrast, the median payment amount for one of the peer-reviewed journals ($146,159.48, Journal of Clinical and Aesthetic Dermatology (JCAD)) was 11 times greater than the next highest median payment for peer-reviewed journals ($12,526.52, Journal of respectively. 4,6,23 Historically, collaboration between physicians and the pharmaceutical industry has resulted in innovations and advancements in medicine. When conducted properly, the relationship between physicians and industry serves to advance the field of medicine as a whole with the ultimate goal of the lives of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was higher than the percentage reported for dermatology textbook authors (54%) and the percentages reported in the studies by Feng et al and Checketts et al, 73.3% and 86% respectively. 4,6,23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation